2018
DOI: 10.1016/j.earlhumdev.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged furosemide exposure and risk of abnormal newborn hearing screen in premature infants

Abstract: Prolonged furosemide exposure was associated with a positive, but not statistically significant, difference in abnormal hearing screening in premature infants. Additional studies with post-hospital discharge audiology follow-up are needed to further evaluate the safety of furosemide in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Infants less than 32 weeks gestational age are the most vulnerable given their kidney immaturity [33]. Previous research showed that preterm infants are commonly exposed to prolonged treatment with average exposure duration of at least 12 days [1,36]. Furthermore, recent data show that preterm newborns exposed to furosemide suffer from more severe comorbidities than unexposed patients [6,19,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants less than 32 weeks gestational age are the most vulnerable given their kidney immaturity [33]. Previous research showed that preterm infants are commonly exposed to prolonged treatment with average exposure duration of at least 12 days [1,36]. Furthermore, recent data show that preterm newborns exposed to furosemide suffer from more severe comorbidities than unexposed patients [6,19,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that preterm infants are commonly exposed to prolonged treatment with average exposure duration of at least 12 days [1,36]. Furthermore, recent data show that preterm newborns exposed to furosemide suffer from more severe comorbidities than unexposed patients [6,19,36]. Indeed, long-term exposure to furosemide (greater than 14 days) in extremely preterm infants warrants even closer monitoring of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors affecting hearing impairments ware shown in therefore, it should be of priority in neonatal care 16,17) . 8,10,11,18) . The ototoxicity of aminoglycoside de pends on treatment duration, serum peak and trough concentra tions, concomitant diseases, and the simultaneous administra tion of loop diuretics and/or vancomycin.…”
Section: Resultsmentioning
confidence: 99%
“…( 17 ) Similarly, in a retrospective study of more than 7000 infants, Gopel et al found no association between aminoglycosides and hearing loss ( 18 ). Wang et al also found there was no statistically significant difference in abnormal hearing screening in 1020 premature babies who were exposed to prolonged furosemide ( 19 ). Despite historical concerns, a large body of evidence now supports the favorable safety profile of vancomycin, aminoglycosides and furosemide, mainly because of conservative dosing regimens in neonates and dose modification of drugs based on serum levels ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%